Digital imaging as scoring method for spittlebug tolerance in Urochloa humidicola hybrids - CGIAR Research Program on Livestock (2020)
Comparison of single-photon avalanche diode (SPAD) measurements and digital images, visual scoring by an inexpert evaluator, and expert visual scoring, indicates that the digital imaging method for phenotyping developed by CIAT and available for uptake might improve the efficiency of breeding for increased tolerance to spittlebugs in U. humidicola.